A eleição parlamentar no Mercosul - Mariano, Karina Pasquariello [UNESP] (Instituto Brasileiro de Relações Internacionais, 2011)
Este artigo analisa a representação parlamentar no Mercosul e as implicações da institucionalização do Parlasul, expondo como este foi pensado e os desdobramentos de sua institucionalização, tendo presente uma preocupação em identificar mudanças ocorridas a partir de sua atuação, e de sua relação com os órgãos decisórios do Mercosul e os Congressos Nacionais.

This article examines the parliamentary representation in Mercosur and the implications of the institutionalization of Parlasur, exposing how it was meant and the consequences of its institutionalization. Its aim is to identify changes and its relationship with policy-making bodies of Mercosur and National Congresses.
Parliamentary election in Mercosur
Keywords: Integração; Mercosul; Parlasul; Integration; Mercosur; Parlasur